The Tower of Babble: Mother Tongue and Multilingualism in India - Sharma, Susheel Kumar (Lesya Ukrainka Eastern European National University, 2017)
Since ancient times India has been a multilingual society and languages in India have thrived though at times many races and religions came into conflict. The states in modern India were reorganised on linguistic basis in 1956 yet in contrast to the European notion of one language one nation, majority of the states have more than one official language. The Linguistic Survey of India (LSI) conducted by Grierson between 1866 and 1927 identified 179 languages and 544 dialects. The first post-independence Indian census after (1951) listed 845 languages including dialects. The 1991 Census identified 216 mother tongues were identified while in 2001 their number was 234. The three-language formula devised to maintain the multilingual character of the nation and paying due attention to the importance of mother tongue is widely accepted in the country in imparting the education at primary and secondary levels. However, higher education system in India impedes multilingualism. According the Constitution it is imperative on the “Union to promote the spread of the Hindi language, to develop it so that it may serve as a medium of expression for all the elements of the composite culture of India … by drawing, wherever necessary or desirable, for its vocabulary, primarily on Sanskrit and secondarily on other languages.” However, the books translated into Hindi mainly from English have found favour with neither the students nor the teachers. On the other hand, the predominance of English in various competitive examinations has caused social discontent leading to mass protests and cases have been filed in the High Courts and the Supreme Court against linguistic imperialism of English and Hindi. The governments may channelize the languages but in a democratic set up it is ultimately the will of the people that prevails. Some languages are bound to suffer a heavy casualty both in the short and long runs in the process. Із давніх часів Індія була багатомовним суспільством, і мови в Індії процвітали, хоча й виникали конфлікти серед багатьох рас і релігій. Штати сучасної Індії були реорганізовані на лінгвістичній основі в 1956 році, але на відміну від європейського поняття однієї мови для однієї нації, більшість індійських штатів мають кілька офіційних мов. Лінгвістичнe опитування Індії, проведене Грірсоном в 1866–1927 рр., дало змогу виокремити 179 мов та 544 діалектів. Перший індійський перепис після здобуття Індією незалежності (1951 р.) визначив 845 мов, включаючи також діалекти. Переписом 1991 року було визначено 216 рідних мов, тоді як в 2001 році їх кількість становила 234. Тримовна формула, що спрямована на збереження багатомовності нації та приділення належної уваги важливості рідної мови, широко прийнята в країні на рівні надання початкової та середньої освіти. Однак система вищої освіти в Індії перешкоджає багатомовності. Відповідно до Конституції: “Держава має сприяти розповсюдженню мови гінді, розвивати її так, щоб вона могла слугувати засобом вираження для всіх елементів складної культури Індії ..., шляхом залучення, де це необхідно або бажано, її словника, головним чином на санскриті, а далі вже на інших мовах”. Проте книги, перекладені на гінді переважно з англійської, не користуються популярністю ні серед студентів, ні серед вчителів. З іншого боку, переважання англійської мови в різних конкурсних іспитах спричинило соціальне невдоволення, яке призвело до масових акцій протесту, а також подання нових справ на розгляд до Вищого та Верховного судів проти мовного імперіалізму англійської та гінді. Влада може визначати мови, проте в умовах демократії переважає думка народу. Незважаючи на це, автор зазначає, що деякі мови приречені зазнати важкої втрати як у короткостроковій, так і в довгостроковій перспективі.
Keywords: language; bilingualism; multi-lingualism; mother tongue; linguistic imperialism; the Constitution; schedule; мова; двомовність; багатомовність; рідна мова; мовний імперіалізм; конституція; графік